Efficient Tn10 transposition into a DNA insertion hot spot in vivo requires the 5-methyl groups of symmetrically disposed thymines within the hot-spot consensus sequence. - Lee, S Y (1987)
Transposon Tn10 inserts preferentially at particular insertion "hot spots" that share a symmetrical 6-base-pair consensus sequence: 5' GCTNAGC 3'. The protein that recognizes this sequence is not known but is likely to be the Tn10-encoded transposase protein. We present evidence that the 5-methyl groups of the two thymines in this sequence are essential for efficient transposon insertion; in their absence the sequence is still recognized, but at lower efficiency. We have reached this conclusion by examination of a specific hot spot whose sequence is 5' GCCAGGC 3'. The innermost cytosines of this sequence happen to be substrates for methylation at their 5 positions by the bacterial dcm-encoded methylase. We find that Tn10 transposes into this site 15 times more frequently in a Dcm+ host than in a Dcm- host; in the Dcm- host, insertions still occur, but at a low frequency. Thus, at this site, the absence of pyrimidine 5-methyl groups at the third positions of the consensus sequence is sufficient to convert a strong insertion hot spot into a weaker but still recognizable hot spot. This observation supports the general proposition, suggested previously by comparisons among consensus sequences, that the presence or absence of these 5-methyl groups is one major feature that can make the difference between a strong and a weak Tn10 insertion hot spot.